Improvement of current withstand capacity of high gradient ZnO varistors. Issue 24 (15th December 2022) - Kong, Anting; Ren, Xin; Ruan, Xuejun; Zhong, Meilian; Lao, Xuebin; Jiang, Haibo; Yao, Zheng; Shi, Liyi
Abstract: The effects of the dispersant and the inorganic high resistance coating on the microstructure and the electrical properties of the ZnO varistors, especially on the current withstand capacity, were studied. The results showed that under the premise of adequate slurry dispersion, when the dispersant content was the minimum, the porosity of the varistor was the minimum, and the current withstand capacity was up to 24 A/cm 2 in 2 ms square waveform impulse test. By coating a high resistance layer with high proportion of spinel forming elements, the content of spinel near the side of the varistor ceramic was increased, thus increasing the resistivity and alleviating the current impact near the edge. The current withstand capacity of 2 ms square waveform impulse was upgraded to 32 A/cm 2 .